Sensing and self: a haptic 'look' at the aesthetics of women's labour in contemporary Maghrebi and Maghrebi-French diasporic cinema. - Sokol, Che (French Screen Studies, 2024)
This article expands on an ongoing dialogue about representations of female protagonists' sensual and embodied experiences in Francophone North African cinema scholarship. It examines the dynamic cinematographic styles of contemporary Maghrebi French filmmakers Abdellatif Kechiche, Nadia El Fani, Leila Kilani and Houda Benyamina, asserting that they create a multisensory connection with the viewer that disrupts the underlying unequal power dynamic between film viewer and the Maghrebi woman's body. This article places labour practices as the loci of analysis, as these examples of quotidian life represent a microcosm of protagonists' participation in larger social and economic frameworks. First, it looks at the role of embodied labour in strengthening a protagonist's connection to her community in Kechiche's La Graine et le mulet/The Secret of the Grain (2007) and El Fani's Bedwin Hacker (2003). Then, it turns to labour practices in Kilani's Sur la planche/On the Edge (2011) and Benyamina's Divines (2016) that isolate and disconnect the protagonist from her community and her body. This article concludes that it is the distinctly multisensory style used by all four directors that centres their protagonists' physical, lived experiences while challenging the viewer not to merely watch them passively, but to engage in a dynamic, empathetic relationship with the body onscreen.